Students' critical thinking ability in implementing the physics learning module with inquiry strategies based on blended learning - Chandra Ertikanto; Ismu Wahyudi (Universitas Sultan Ageng Tirtayasa, 2023)
The revised 2013 curriculum demands that teachers at all types and levels of schools are expected to be able to apply various approaches and learning models. The problem is the need for learning approaches, models, and assessment instruments for the National Examination or School Examination. This study aimed to describe the difference in the average critical thinking ability of students who used a scientific approach learning module with an inquiry strategy based on blended learning and conventional books used in one of the public high schools in Bandar Lampung. After carrying out the learning process using these modules in the experimental class and the learning process using conventional books in the control class, an analysis of gathering information through discussion forums and planning, instrument testing, difficulty level, discriminating power, N-gain, and Independent Sample T-test is carried out. Test. The final results of the research can be concluded that learning modules using a scientific approach with inquiry strategies based on blended learning can improve the critical thinking skills of high school students in Bandar Lampung for the 2020/2021 academic year.